Layanan Psikologi Konseling BNPB Melalui Metode Psychological First Aid Secara Online pada Masa Pandemi COVID-19 - Aisyah Syihab (Fakultas Psikologi Universitas Pancasila, 2022)
One of handling the COVID-19 pandemic that carried out by BNPB is to form a volunteers of psychology, to provide psychological counseling services to communities those affected by the pandemic. Psychological counseling services are carried out online using the psychological first aid methods. This service is a form of community service that is carried out remotely through the Zoom Meeting. The advantage of it is that reaches more people throughout Indonesia, even for those who have never previously received counseling psychology services. One of the psychological counseling services is provided to a housewife who lives in Solo, while the counselor provides services from Jakarta. The service is provided in two meetings via Zoom Meeting with each meeting lasting 2 hours. After twice receiving psychological counseling services using the psychological first aid methods, especially training on grounding techniques when experiencing stress, the client felt much better. Although this counseling psychology service is provided remotely where there are some obstacles, it still has a positive impact on clients.